China's strategic arsenal : worldview, doctrine, and systems - Smith, James M., 1948-; Bolt, Paul J., 1964- (Georgetown University Press, 2021)
"A critical look at how China's growing strategic arsenal could impact a rapidly changing world order"--Publisher's website.